La transformation des « communs » à Roşia-Montană : Quel régime de propriété pour quel développement ? - Radu C. Barna (Revue de Géographie Alpine)
In the 18th-19th centuries, Roşia-Montană, a village in the Carpathian Mountains of Transylvania (Apuseni), Romania, has been privy to a period of prosperity due to the gold ore existing in the area, but also a period of social and cultural bloom due to the autonomy awarded by the government in Vienna (Transylvania was at the time a province in the Habsburg empire). The community of this village structured around some common goods owing to the harsh environment of mountain living conditions, as well as to the risks inherent to the mining activity. Communism and the following transition towards the market economy reduced the autonomy and transferred properties to the State and subsequently to multinational companies. This had a significant impact on said goods. All these changes then determined the inhabitants to structure around a new “common”.In order to highlight the positive influence of commons on the development, this article performs a historic analysis of the four cornerstone periods of Roşia-Montană. Each of these has witnessed a specific property regimen and specific freedoms of action. Therefore, for each stage we aimed to highlight the degree of co-activity in the life of the people, their capacity to convert the gold ore into real freedom and the satisfaction of their varied needs. This is how we were able to conclude that there is an ongoing connection between commons and development.